Pengaruh Budaya Organisasi Dan Iklim Organisasi Terhadap Prestasi Kerja Widyaiswara (Study Kasus Di UPT-D Provinsi Riau, Pekanbaru) - . Dollar (Jurnal Transformasi Administrasi, 2018)
This study aims to determine the effect of organizational culture and organizational climate on Instructors’ performance in Technical Implementation Unit Education and Training Civil Servant Riau Province. This study employs both quantitative and qualitative approach. The sample is purposive sampling of 40 instructors. Data collection techniques used in this study using questionnaires and interviews on the problems studied. To assess the influence of organizational culture and organizational climate on the work pretation of the instructor data analysis used is multiple linear. The result shows that there is an effect of organizational culture and organizational climate on the work performance of Instructor in Technical Implementation Unit of Education and Training of Riau Province.